2022
DOI: 10.1002/iju5.12534
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous robot‐assisted nephroureterectomy and radical cystectomy

Abstract: Introduction We present a case of simultaneous robot‐assisted radical nephroureterectomy (RANU) and robot‐assisted radical cystectomy (RARC) for muscle‐invasive bladder cancer with concomitant upper urinary tract urothelial carcinoma. Case presentation A 59‐year‐old Japanese man was diagnosed with right ureteral cancer and muscle‐invasive bladder cancer. We performed RANU and RARC simultaneously; three of the ports used for RANU were diverted to RARC. Console times for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…This notion and corresponding causality is supported by Yajima et al, who reported the rst case of combined RANU and RARC in Japan. They reported RANU console time to be 66 (RANU) and 207 (RARC) minutes which is in accordance with our ndings (42 minutes for RANU in group 2) (17). Moreover, Kamei et al compared the en-bloc cystectomy with radical nephroureterectomy between 17 open-surgical and 10 robot-assisted patients and found the minimally invasive approach to be non-inferior (23).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This notion and corresponding causality is supported by Yajima et al, who reported the rst case of combined RANU and RARC in Japan. They reported RANU console time to be 66 (RANU) and 207 (RARC) minutes which is in accordance with our ndings (42 minutes for RANU in group 2) (17). Moreover, Kamei et al compared the en-bloc cystectomy with radical nephroureterectomy between 17 open-surgical and 10 robot-assisted patients and found the minimally invasive approach to be non-inferior (23).…”
Section: Discussionsupporting
confidence: 86%
“…Data is still very limited, but RANU is increasingly utilized in the surgery of UTUC (15,16). For example, Yajima et al reported a case of simultaneous RANU with robot-assisted radical cystectomy (RARC) (17). Thus, we investigated the complications and oncological outcomes of robot-assisted radical nephroureterectomy (RANU) and robot-assisted segmental ureterectomy (RASU) patients in a referral urological department performed by a single robotic expert surgeon.…”
Section: Introductionmentioning
confidence: 99%
“…In this report, the console time was 150 min for RANU and 142 min for RATLH, for a total operative time of 379 min, that is, 87 min of nonconsole time. In our previous report on simultaneous RANU and RARC procedures, the total operative time was 386 min, with a console time of 66 min for RANU and 207 min for RARC, where the nonconsole time was 113 min 5 . Although it must be taken into account that the simultaneous RANU/RARC surgery needed additional time to create the cutaneous ureterostomy, nonconsole time was not short for simultaneous RANU/RATLH surgery or RANU/RARC surgery.…”
Section: Discussionmentioning
confidence: 95%
“…In our previous report on simultaneous RANU and RARC procedures, the total operative time was 386 min, with a console time of 66 min for RANU and 207 min for RARC, where the nonconsole time was 113 min. 5 Although it must be taken into account that the simultaneous RANU/RARC surgery needed additional time to create the cutaneous ureterostomy, nonconsole time was not short for simultaneous RANU/RATLH surgery or RANU/RARC surgery. For multiple cumbersome procedures such as docking/redocking the robot, repositioning, and inserting new ports, it might be possible to reduce nonconsole time even more by training not only physicians but also nurses and other bedside assistants as a team.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation